1998
DOI: 10.1038/915
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the gene responsible for Best macular dystrophy

Abstract: Best macular dystrophy (BMD), also known as vitelliform macular dystrophy (VMD2; OMIM 153700), is an autosomal dominant form of macular degeneration characterized by an abnormal accumulation of lipofuscin within and beneath the retinal pigment epithelium cells. In pursuit of the disease gene, we limited the minimum genetic region by recombination breakpoint analysis and mapped to this region a novel retina-specific gene (VMD2). Genetic mapping data, identification of five independent disease-specific mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
445
3
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(462 citation statements)
references
References 28 publications
6
445
3
7
Order By: Relevance
“…Mutations in the BEST1 gene were incriminated in Best disease by Petrukhin et al in 1998 [7]. The gene product of BEST1, bestrophin, was previously postulated to act as an calcium-sensitive chloride channel in the basolateral cell membrane of the retinal pigment epithelium however a recent study showed that bestrophin is localised in the endoplasmic reticulum membrane, close to the cell membrane [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the BEST1 gene were incriminated in Best disease by Petrukhin et al in 1998 [7]. The gene product of BEST1, bestrophin, was previously postulated to act as an calcium-sensitive chloride channel in the basolateral cell membrane of the retinal pigment epithelium however a recent study showed that bestrophin is localised in the endoplasmic reticulum membrane, close to the cell membrane [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lesions are restricted to the eye without any systemic associations. Petrukhin et al [5], identified the retina-specific gene and designated it as the VMD2.The protein encoded by this gene was proposed to be called bestrophin.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, defects in proteins associated with RPE have been identified (Petrukhin et al 1998;Maw et al 1997;Gu et al 1997). Also, in age related macular degenerations, both the pigment epithelium and the neural retina are affected, and it will therefore be important in these patients to replace both the RPE as well as the neural retina.…”
Section: Discussionmentioning
confidence: 99%